Six novel species of the obligate marine actinobacterium Salinispora, Salinispora cortesiana sp. nov., Salinispora fenicalii sp. nov., Salinispora goodfellowii sp. nov., Salinispora mooreana sp. nov., Salinispora oceanensis sp. nov. and Salinispora vitiensis sp. nov., and emended description of the genus Salinispora. Issue 8 (23rd August 2020) - Román-Ponce, Brenda; Millán-Aguiñaga, Natalie; Guillen-Matus, Dulce; Chase, Alexander B.; Ginigini, Joape G.M.; Soapi, Katy; Feussner, Klaus D.; Jensen, Paul R.; Trujillo, Martha E.
Abstract : Ten representative actinobacterial strains isolated from marine sediments collected worldwide were studied to determine their taxonomic status. The strains were previously identified as members of the genus Salinispora and shared >99 % 16S rRNA gene sequence similarity to the three currently recognized Salinispora species. Comparative genomic analyses resulted in the delineation of six new species based on average nucleotide identity and digital DNA–DNA hybridization values below 95 and 70 %, respectively. The species status of the six new groups was supported by a core-genome phylogeny reconstructed from 2106 orthologs detected in 118 publicly available Salinispora genomes. Chemotaxonomic and physiological studies were used to complete the phenotypic characterization of the strains. The fatty acid profiles contained the major components iso-C16 : 0, C15 : 0, iso-17 : 0 and anteiso C17 : 0 . Galactose and xylose were common in all whole-sugar patterns but differences were found between the six groups of strains. Polar lipid compositions were also unique for each species. Distinguishable physiological and biochemical characteristics were also recorded. The names proposed are Salinispora cortesiana sp. nov., CNY-202 T (=DSM 108615 T =CECT 9739 T ); Salinispora fenicalii sp. nov., CNT-569 T (=DSM 108614 T =CECT 9740 T ); Salinispora goodfellowii sp. nov., CNY-666 T (=DSM 108616 T =CECT 9738 T ); Salinispora mooreana sp. nov., CNT-150 T (=DSM 45549 T =CECT 9741 T ); Salinispora oceanensis sp. nov., CNT-138 T (=DSM 45547 T =CECT 9742 T ); and Salinispora vitiensis sp. nov., CNT-148 T (=DSM 45548 T =CECT 9743 T ).